Implementation of a Web‐Based Patient Simulation Program to Teach Dental Students in Oral Surgery. Issue 2 (1st February 2016) - Weiner, Carina Kruger; Skålén, Maya; Harju-Jeanty, Dick; Heymann, Robert; Rosén, Annika; Fors, Uno; Lund, Bodil
Abstract : The aim of this study was to evaluate a web‐based simulation of patients (Web‐SP) program on learning skills in clinical reasoning and patient evaluation in the oral surgery education of third‐year dental students. A secondary aim was to investigate the program's effect on students' learning, knowledge, and attitudes towards virtual patient simulations. Authentic virtual oral surgery patient cases were created at a dental school in Sweden using the Web‐SP platform. The Web‐SP program was introduced in a two‐hour seminar. A 20‐minute pre‐seminar test (test A) was administered to assess the students' knowledge of oral surgery prior to experiencing the Web‐SP program. Ten days after the seminar, another test (test B) was administered to evaluate the increase in oral surgery knowledge as a result of using the program, and an emailed survey of the students was conducted. Of 70 students in the course, 67 (95.7%) agreed to participate in the study and took test A; of these, 59 (88%) took test B. Of the 59 students who took both tests, 28 (42%) completed the survey. The results of the two tests showed a statistically significant increase in knowledge, which was in accordance with the learning goals (p<0.0001). The survey results showed that the students had a positive attitude towards the teaching method. In this study, Web‐SP was found to be a valuable tool for teaching clinical reasoning and patient evaluation in an undergraduate oral surgery education setting by improving learning outcomes in comparison with traditional teaching alone.